Enhancing Students’ Learning Motivation by Applyıng Reflectıve Pedagogy to Modules for Junıor High School - Agnes, Tri; Asrowi, Asrowi; Sutimin, Leo Agung (International journal of psychology and educational studies, 2019)
The Reflective Pedagogy Paradigm is an art of thinking and doing something thoughtfully that incorporates humanistic values into conscious subjects consciously. This paradigm endorses the meaning of each topic within learning materials based on the students' own experience. Students take into their consciousness life values with learning materials by themselves or by their groups in order that they can practice it in daily life. This study is aimed to develop an eligible module using reflective pedagogy and revealing the impact of the use of module on students’ motivation to study and experience. In this study, the developmental research method was used for resolving learning problems within eight grade of Junior High School Students during the Catholic religion class. ADDIE (analysis, design, development, implementation, and evaluation) model was used as the module development method in this study. This study used the non-test method as the data collection technique with questionnaire and interview as the instruments. The data analysis techniques used in this research were descriptive quantitative methods. The results of this research show that the use of the module in eight graders Junior High Schools categorized as eligible based on media and material experts. Thus, it can be concluded that the module is suitable for use. The improvement appeared after the implementation conducted using the reflective pedagogy module. The result shows that students’ motivation is significantly higher than before using the module according to t-test calculation. The result of post-test and pre-test score is statistically different so that means that the implementation of the reflective pedagogy in religion subject improves learning motivation